Plug-in electric vehicles what role for Washington? - Sandalow, David; ProQuest (Firm) (Washington, D.C. : Brookings Institution Press, 2009)
"Explains the current landscape for plug-in electrics and implications for national security, the environment, and the economy. Discusses what can and should be done by the U.S. government to advance the role of plug-in electric vehicles"--Provided by publisher.
Foreword / Strobe Talbott -- Commentary / Dan Reicher -- Introduction / David Sandalow -- Part One. Benefits -- Geopolitical implications of plug-in vehicles / R. James Woolsey and Chelsea Sexton -- Electrification of transport and oil displacement : how plug-ins could lead to a 50 percent reduction in U.S. demand for oil / Saurin D. Shah -- Pluggable cars : a key component of a low-carbon transportation future / Deron Lovaas and Luke Tonachel -- The cashback car / John Wellinghoff -- Part Two. Barriers -- The impact of plug-in hybrids on U.S. oil use and greenhouse gas emissions / Alan L. Madian, Lisa A. Walsh, and Kim D. Simpkins -- Look before you leap : exploring the implications of advanced vehicles for import dependence and passenger safety / Irving Mintzer -- Part Three. Policies -- Current federal authorized programs on plug-in hybrids, battery electric vehicles, and related efforts / Dean Taylor -- Tax credits for electric cars : stimulating demand through the tax code / Benjamin H. Harris -- Cost-effectiveness of greenhouse gas emission reductions from plug-in hybrid electric vehicles / Daniel M. Kammen ... [et. al.] -- Federal policy options to support early electric vehicle deployment by reducing financial and technological risks / Bracken Hendricks and Benjamin Goldstein -- Electric vehicles : how do we get millions on the road? / Tom Z. Collina and Ron Zucker -- Electric utility issues in replacing oil with electricity in transportation / Steve Marshall -- Promoting use of plug-in electric vehicles through utility industry acquisition and leasing of batteries / Peter Fox-Penner ... [et. al.].
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Electric vehicle industry -- United States; Electric vehicles -- Government policy -- United States; Hybrid electric vehicles -- Government policy -- United States; Electronic books